Resting state fMRI connectivity analysis as a tool for detection of abnormalities in five different cognitive networks of the brain in Multiple Sclerosis patients. Issue 12 (2016) - Nejad-Davarani, Siamak P.; Chopp, Michael; Peltier, Scott; Li, Lian; Davoodi-Bojd, Esmaeil; Lu, Mei; Bagher-Ebadian, Hassan; John, John; Gallagher, David; Ding, Yue; Hearshen, David; Jiang, Quan; et al.
No abstract available